Schematic topological modeling of signal transducers for analytical microsystems-on-crystal - Dovgiy, V.V.; Holota, V.I.; Kohut, I.T. (Physics and Chemistry of Solid State, 2015)
The paper presents the results of circuit design and computer simulation of signal transducers for integrated circuits and silicon-on-insulator (CMI) ICs.